The impact of Basel III on money creation: A synthetic theoretical analysis - Wanting Xiong; Yougui Wang (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
Inspired by the extensive criticisms against the textbook fractional reserve theory, this paper revisits the mechanics of money creation process and complements the traditional focus on the reserve requirement by elaborating on the roles of three prudential regulations proposed in the Basel III accord. In particular, the authors consider such conditions where the financial markets are imperfect and suffer from various frictions that the commercial bank cannot readily modulate their liquidity and capital buffers, especially at an aggregate level or within a short period. Meanwhile, as a result of maturity mismatch and fundamental uncertainty, the credit and money creation activities inevitably add to the liquidity and insolvency risks faced by the bank. Under the assumptions that the levels of bank reserves, capital and government bonds are exogenously given, and that the concerned prudential regulations are always binding, the authors examine the determinants of the broad money aggregate and the money multiplier. Specifically, they find that 1) the money multiplier under Basel III is not constant but a decreasing function of the monetary base; 2) the determinants of the bank's money creation capacity are regulation specific; 3) when multiple regulations are imposed simultaneously, the effective binding regulation and the corresponding money multiplier will vary across different economic states and bank balance sheet conditions.
Keywords: E51; G28; G18; E60; 330; money creation; Basel III; liquidity coverage ratio; capital adequacy ratio; leverage ratio; money multiplier